Manufacture of High-Protein, Micronutrient Breakfast Cereals With Local Raw Materials and Their Physical and Chemical Characteristics - Salim, Dina Kamal; Saleh, Abeer Majeed; Mustafa, Entisar Dawood (American Journal of Botany and Bioengineering, 2026)
This study examined the manufacturing and testing of instant breakfast cereals to create high protein and micronutrient dense breakfast cereal with local raw materials since the additions resulted in an apparent change in the nutritional profile to elevate protein and fiber and reduce carbohydrates without altering the caloric value.ric content. It was also found that the physical, chemical and microbial characteristics of the product were within reasonable ranges and that there was a significant difference in crispness and shelf life. In contrast, sensory evaluation was negatively affected at high addition levels. Treatments T1 and T2 achieved the best balance between sensory acceptability and nutritional value, making the local product a promising healthy alternative compared to traditional commercial products. Relevance of the Study, aiding in the creation of nutritious food items rich in vitamins and protein and producing food items with excellent nutritional value by using local raw ingredients, as well as producing superior local substitutes to lessen reliance on imports. Encouraging research in the field of food science and the growth of regional food businesses. Offering food items appropriate for populations that need diets high in protein, such kids and athletes.